STRATEGI OPTIMALISASI PENGGUNAAN MEDIA SOSIAL YANG AMAN DAN SEHAT UNTUK GEN ALPHA - Sapitri , Tania; Apriani, Mutia; Putri, Zahra Amelia; Monica, Dede Rahma; Ardiansyah, M Rakha; Huda, Fadilah Nurul; Nurafni, Nazla; Halika, Jasmin Nazwa; Annastasya G, Diesta; Syabani, Azzahra Rizkia; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2024)
In this era of globalisation, social media is now an essential part of the daily lives of teenagers around the world. Teenagers can quickly connect with their friends, share experiences, and access various information thanks to technological advances and easy access. Based on the summary above, our service group from Siliwangi University socialised ‘Optimising the use of social media in a healthy and safe manner’ which was held at SMPN 11 Tasikmalaya city which is located on Jl.Cilendek No.11 A. Ciberem Tasikmalaya City. The target of the service programme is students at SMPN 11 Tasikmalaya City, which amounts to about 38 people in the library room. This activity presents material on the importance of parenting through healthy and safe use of social media as an effort to reduce social media addiction in adolescents, especially in adolescents at SMPN 11 Tasikmalaya City. This socialisation is expected to provide a learning tool in the future and make a positive contribution to the use of social media both from virtual and real interactions.